2020
DOI: 10.34172/jlms.2020.66
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Disinfection With a 445 nm Diode Laser Within the Scope of Restorative Therapy – A Pilot Study

Abstract: Introduction: Cavity disinfection is necessary to prevent a progressive infection of the crown dentin and pulp. Increasing intolerance and resistance to antiseptics and antibiotics as well as the controversy over the effects of those on the dental hard tissue and composite have prompted the investigation of alternative treatment options. The objective of this pilot study is to evaluate the antibacterial potential of a diode laser with a wavelength of 445 nm in the cavity preparation using the bacterium Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…The changes in sensitivity of bacteria to an antibiotic after exposure to diode laser are affected by a different laser aspects such as wavelength, the intensity of energy, time of exposure, and modality of propagation of laser irradiation [11], [21]. Also, exposure to diode laser may cause changes in bacterial efflux pump that accounted for bacterial resistance to antibiotics such as Beta-lactams and aminoglycoside [43]. In addition, it may cause bacterial failure in the production of target enzymes that chemically modified a special antibiotic leading to increased bacterial sensitivity to these antibiotics [13].…”
Section: Effects Of Diode Laser On Viability and Antibiotic Sensitivi...mentioning
confidence: 99%
“…The changes in sensitivity of bacteria to an antibiotic after exposure to diode laser are affected by a different laser aspects such as wavelength, the intensity of energy, time of exposure, and modality of propagation of laser irradiation [11], [21]. Also, exposure to diode laser may cause changes in bacterial efflux pump that accounted for bacterial resistance to antibiotics such as Beta-lactams and aminoglycoside [43]. In addition, it may cause bacterial failure in the production of target enzymes that chemically modified a special antibiotic leading to increased bacterial sensitivity to these antibiotics [13].…”
Section: Effects Of Diode Laser On Viability and Antibiotic Sensitivi...mentioning
confidence: 99%
“…Studies in the literature have shown that diode laser treatment at 445 nm prevents enamel demineralization and cavity disinfection [ 26 , 27 , 28 ]. The results of this study agree that 445 nm is the best wavelength, and the results presented herein show that using a femtosecond laser with Moringa oleifera not only prevents demineralization but in fact causes remineralization.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the infiltration of bacteria into the dentinal tubules, the depth of the dentinal tubules cannot be properly cleared by the conventional methods [24,25]. erefore, to investigate the effects of dentin thickness on the bactericidal effects of the lasers, unlike previous studies in which the bacterial suspension was directly inoculated into the root canal and the laser fiber tip was in direct contact with the bacteria inside the dental canal [26], in this study, the dentinal sections with thicknesses of 300, 500, and 1,000 μm were prepared and indirect laser irradiation was used, i.e., the laser fiber was placed on the opposite side of the bacterial suspension.…”
Section: Discussionmentioning
confidence: 99%